Knowledge, attitude and behaviour among undergraduates from the science and technology fields towards climate change / Sharir Aizat Kamaruddin ...[et al.] - Asman, Siti Nuratiqah; Yacoob, Aina Najwa; Amir, Asymiratul Najihah; Hamka, Nurul Zafirah; Bojeng, Nur Rosyidah; Kamaruddin, Sharir Aizat (Universiti Teknologi MARA Cawangan Pahang, 2021)
This exploratory study aims to investigate the knowledge and attitude of undergraduate science and technology students towards climate change. In December 2020, an online questionnaire has been distributed to undergraduate students in the field of science and technology. Collected data were made for demographic information, knowledge, attitude and behaviour towards climate change. The survey found that there were a total of 166 respondents which consists of 31.71% male students and 68.29% female students around 18 to 26 years old. Most of the respondents believed that climate change has happened, and negative impacts on human beings can result from climate change. The respondents have multiple understandings in indicating the reason for climate change but many agreed that climate change would promote extreme weather and ecological crisis. The majority of respondents obtained data and materials about climate change from the internet. Moreover, the majority of respondents indicated that they were willing to change their behaviour and wanted to join environmental protection activities relating to climate change. Finally, this research concludes that further actions and awareness need to be enacted especially among undergraduates to combat climate change near future.